Population Dynamics in a Microfounded Predator-PreyModel - Thomas Christiaans (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2004)
This paper analyzes the dynamics of a two-dimensional microfounded predatorprey model. It is shown that the dynamics closely resemble those of a model commonly used in mathematical biology if parameters of the latter are suitably restricted. The positive equilibrium of the microfounded model is globally asymptotically stable for positive initial values largely irrespective of the parameter values chosen. If a version of Allee?s Law is included, however, species extinction becomes possible.
Keywords: Q20; 330; population dynamics; ratio dependence; species extinction; Bioökonomik; Mikroökonomische Fundierung; Biodiversität; Theorie